Important performance characteristics in elite clay and grass court tennis match-play - Fitzpatrick, A.; Stone, J. A.; Choppin, S.; Kelley, J. (International Journal of Performance Analysis in Sport, 2019)
The performance characteristics of elite tennis match-play differ depending on court surface. However, the performance characteristics (e.g. aces, first serve points won, forced errors) most associated with success on different surfaces are currently unknown. With three weeks typically separating Roland Garros and Wimbledon, the transition from clay to grass courts, whereby players must adapt their game style between surfaces, is crucial to understand. Using the recently validated PWOL method, we analysed 984 singles matches across the 2016 and 2017 Roland Garros and Wimbledon tournaments, to identify the most important performance characteristics in clay and grass court tennis. Results revealed that points won of 0-4 shot rally length, first serve points won and baseline points won were most strongly associated with success for both sexes; serve-related characteristics (aces, double faults and average first serve speed) were among the least associated with success. Furthermore, winning short points (points of 0-4 shots) was more closely associated with success than winning medium-length (5-8 shots) and long points (9+ shots). To be representative of match-play, findings suggest that players should afford sufficient practise time to short rallies and point-ending strategies during the clay and grass court seasons, rather than over-emphasising long rallies.